Qur'anic Studies between University Theology and the Humanities: A Field Worth Cultivating? - Hoffmann, Thomas Jøhnk (Islam and Christian-Muslim relations, 2018)
This essay considers some of the past, present and possible future contexts and prospects of qur'anic studies in a Western academic context, particularly within the contested confines of so-called university theology and its sister disciplines of religion and cultural studies. It argues that qur'anic studies can and should cross - but not leave - its traditional borders within the humanities and re-engage with theological studies, and vice versa. This also includes a plea for a new recognition of committed and experimental readings, since scholarship inevitably implies an element of intervention and engagement, even when pursued with the strictest ideals of objectivity or fairness in mind. Therefore, a number of motivations for a renewed relevance of qur'anic studies within the orbit of university theology are adduced.